Cigarette Smoke-Induced Pulmonary Inflammation Becomes Systemic by Circulating Extracellular Vesicles Containing Wnt5a and Inflammatory Cytokines - Feller, Diana; Kun, Jozsef; Ruzsics, Istvan; Rapp, Judit; Sarosi, Veronika; Kvell, Krisztian; Helyes, Zsuzsanna; Pongracz, Judit E. (Frontiers in Immunology, 2018)
Chronic obstructive pulmonary disease (COPD) is a devastating, irreversible pathology affecting millions of people worldwide. Clinical studies show that currently available therapies are insufficient, have no or little effect on elevated comorbidities and on systemic inflammation. To develop alternative therapeutic options, a better understanding of the molecular background of COPD is essential. In the present study we show that non-canonical and pro-inflammatory Wnt5a is up-regulated by cigarette smoking with parallel up-regulation of pro-inflammatory cytokines in both mouse and human model systems. Wnt5a is not only a pro-inflammatory Wnt ligand but can also inhibit the anti-inflammatory PPAR gamma transcription and affect M1/M2 macrophage polarisation. Both Wnt5a and pro-inflammatory cytokines can be transported in lipid bilayer sealed extracellular vesicles (EV-s) that reach and deliver their contents to every organ measured in the blood of COPD patients therefore demonstrating a potential mechanism for the systemic nature of this crippling disease.